High resolution integrative analysis reveals widespread genetic and epigenetic changes after chronic in‐vitro acid and bile exposure in barrett's epithelium cells. Issue 12 (3rd October 2013) - Bajpai, Manisha; Kessel, Rachel; Bhagat, Tushar; Nischal, Sangeeta; Yu, Yiting; Verma, Amit; Das, Kiron M.
<x xml:space="preserve">Abstract</x> Barrett's epithelium (BE) is a premalignant condition resulting from chronic gastroesophageal reflux that may progress to esophageal adenocarcinoma (EAC). Early intervention holds promise in preventing BE progression. However, identification of high‐risk BE patients remains challenging due to inadequate biomarkers for early diagnosis. We investigated the effect of prolonged chronic acid and bile exposure on transcriptome, methylome, and mutatome of cells in an in‐vitro BE carcinogenesis (BEC) model. Twenty weeks acid and bile exposed cells from the BEC model (BEC20w) were compared with their naïve predecessors HiSeq Illumina based RNA sequencing was performed on RNA from both the cells for gene expression and mutational analysis. HELP Tagging Assay was performed for DNA methylation analysis. Ingenuity pathway, Gene Ontology, and KEGG PATHWAY analyses were then performed on datasets. Widespread aberrant genetic and epigenetic changes were observed in the BEC20w cells. Combinatorial analyses revealed 433 from a total of 863 downregulated genes had accompanying hypermethylation of promoters. Simultaneously, 690 genes from a total of 1, 492 were upregulated with accompanying promoter hypomethylation. In addition, 763 mutations were identified on 637 genes. Ingenuity pathway analysis, Gene Ontology, and KEGG PATHWAY analyses associated the genetic and epigenetic changes in BEC20w cells with cellular and biological functions. Integration of high resolution comparative analyses of naïve BAR‐T and BEC20w cells revealed striking genetic and epigenetic changes induced by chronic acid and bile exposure that may disrupt normal cellular functions and promote carcinogenesis. This novel study reveals several potential targets for future biomarkers and therapeutic development. © 2013 Wiley Periodicals, Inc.